2020
DOI: 10.5902/2179460x41392
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and identification of essential oil components from the leaves of Syzygium malaccense (L.) MERR. & L.M. PERRY, MYRTACEAE

Abstract: Popularly known as red jamb, the species Syzygium  malaccense (L.) Merr. L.M. Perry is an Asian tree from India, Malaysia, Vietnam and Thailand that has adapted to the climate and soil of the North, Northeast and Southeast of Brazil. The antioxidant and anti-inflammatory activities of this species have already been cited in the literature. This study aimed to extract and identify the essential oil constituents of the leaves of this species. The leaves were dried and ground; and the essential oil was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Leaf yield of S. cumini was reported to be 0.56% in Cairo-Egypt (Mohamed, Ali & El-Baz 2013), 0.05% in Rio de Janeiro (Siani et al, 2013), in Maranhão (Brazil) 0.52% and in Pakistan 0.03% (Hanif et al, 2020). As for the leaves of S. malaccense, a yield of 0.15% was reported in Ifé in Nigeria (Karioti, Skaltsa & Gbolade 2007), 0.0297% in the city of Kuala Selagor (Malaysia) (Ismail, Ismail & Lajis et al, 2010) and 0.03% in Paraná (Brazil) (Feltrin et al, 2020). And for the leaves of S. jambos, information on their yield was not found in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaf yield of S. cumini was reported to be 0.56% in Cairo-Egypt (Mohamed, Ali & El-Baz 2013), 0.05% in Rio de Janeiro (Siani et al, 2013), in Maranhão (Brazil) 0.52% and in Pakistan 0.03% (Hanif et al, 2020). As for the leaves of S. malaccense, a yield of 0.15% was reported in Ifé in Nigeria (Karioti, Skaltsa & Gbolade 2007), 0.0297% in the city of Kuala Selagor (Malaysia) (Ismail, Ismail & Lajis et al, 2010) and 0.03% in Paraná (Brazil) (Feltrin et al, 2020). And for the leaves of S. jambos, information on their yield was not found in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are also reports of the classes of volatile compounds from S. malaccense, in which Karioti, Skaltsa & Gbolade (2007), found 41.6% of monoterpene hydrocarbons and 25.5% of sesquiterpene hydrocarbons, already Lawal et al (2014), reported that monoterpene hydrocarbons, corresponded to 79.9% of the volatile oil composition of the leaves. Feltrin et al (2020), found 68.76% of sesquiterpenes and 29.12% were oxygenated sesquiterpenes.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Herein, the intended EOs have been extracted using three methods: hydrodistillation (HD), supercritical fluid (SF), and headspace (HS). Interestingly, the HD method has been previously implemented for the extraction of the EO from both species but from different geographical origins [ 38 41 ]. Conversely, this is the first report on the extraction of EOs from both species using state-of-the-art approaches such as supercritical fluid (SF), and head-space (HS).…”
Section: Discussionmentioning
confidence: 99%